A pharmacy-led United States Pharmacopeia (USP) chapter 800 compliance collaborative at an academic medical center. (15th May 2018) - Mekoba, Bijan C.; Turingan, Erin M.; Roberts, Patricia A.; Mason, Susan; Willoughby, Ian; Taylor, Cindy; Stivers, Andrew; Valgus, John
Abstract : Purpose: One academic medical center's efforts to move toward compliance with requirements of United States Pharmacopeia ( USP ) chapter 800 through a multidepartmental collaborative initiative are described. Summary: Requirements of USP general chapter 800 (enforceable as of December 2019) address the handling of hazardous drugs (HDs) throughout the entire operational and clinical cycle, from receiving to compounding, administration, and waste disposal. Due to the variety of pharmacy operational areas in which HDs are encountered at University of North Carolina Medical Center (UNCMC), multiple pharmacy managers oversee the safe handling of HDs. To determine baseline compliance with USP chapter 800 requirements, a common assessment tool was developed to ensure a standardized approach to compliance assessment in all areas. An interdepartmental workgroup was created to ensure institutionwide support for a collaborative compliance initiative, a uniform understanding of compliance risks, and robust action planning. UNCMC has taken a number of steps toward USP chapter compliance in areas such as engineering controls, environmental quality and controls, use of personal protective equipment, hazard communication programs, personnel training, spill control, and medical surveillance. Conclusion: Achieving USP chapter 800 compliance presented several operational, clinical, and financial challenges for the medical center, requiring months of preparation and diligence by the hospital leadership. The pharmacy department–led compliance collaborative allowed departments to proactively align while implementing practice and quality standards to foster safety for patients, workers, and the environment.